The Bullshit Doctrine: Fabrications, Lies, and Nonsense in the Age of Trump - Kristiansen, Lars J.; Kaussler, Bernd (Informal Logic)

(untitled) (Informal Logic, 2018)
Guided by the concept of bullshit, broadly defined as a deceptive form of rhetoric intended to distract and/or persuade, we examine how fabrications and false statements— when crafted and distributed by the president of the United States—impact not only foreign policy making and implementation but also erode democratic norms. Unconstrained by reality, and seemingly driven more by celebrity and showmanship than a genuine desire to govern, we argue that President Trump’s penchant for bullshit is part of a concerted strategy to sideline critics while simultaneously undermining the ongoing investigations into the Trump campaign’s alleged collusion with the Russian government.